Analysis of Brand Crisis Public Relations: Take FuYao Glass Brand Crisis in 2014 as an Example - Chen, Yidan (International Journal of Social Sciences and Public Administration, 2024)
This article delves into the case of Fuyao Glass, a Chinese company that purchased a General Motors assembly plant in Dayton, Ohio, in 2014, investing heavily to establish operations in 2016. Amid speculation about the company’s business focus shifting to the United States, Chairman Cao Dewang reassured the public that their primary focus remains in China. However, the incident highlighted the importance of crisis communication in the new media era, where crises can spread rapidly and have far-reaching consequences. Understanding public relations as a means of managing relationships between organizations and the public is crucial, especially in crisis situations. The text emphasizes the need for proactive crisis management strategies, including real-time monitoring of public opinion and the development of contingency plans. Additionally, it underscores the significance of corporate social responsibility in maintaining a positive brand image and navigating crises effectively. Ultimately, the article underscores the importance of strategic communication and crisis preparedness in safeguarding a company’s reputation and mitigating potential risks.